The ART of resilience: a theoretical bridge across resilience perspectives - Farchi, Moshe U.; Peled-Avram, Maya (Frontiers in Psychology, 2025)
The theoretical understanding of psychological resilience has evolved significantly over recent decades, leading to diverse conceptual frameworks that emphasize different aspects of resilient adaptation. Some frameworks focus on resilience as a personal trait, others view it as a dynamic process, while still others emphasize the role of environmental and systemic factors. This theoretical paper introduces the ART framework (Acknowledgment, Reframe, and Tailoring), which provides an integrative perspective that bridges these seemingly disparate approaches. The ART framework offers a comprehensive understanding of how various resilience mechanisms work together in real-world contexts by focusing on the dynamic interplay between resource identification, reframing threats as challenges, and adaptive tailoring between resources and challenges. The ART framework incorporates and extends existing theoretical perspectives while providing a practical structure for understanding resilience development and intervention.